The Analysis of Economic Income and Consumption Structure of Rural Residents: A Grey Relational Analysis Model - Junjuan Wang (Engineering Reports, 2025)
ABSTRACT Taking the economic income and consumption structure data of rural residents in Henan Province from 2006 to 2020 as an example, the change from 2006 to 2020 was briefly introduced, and then the relationship between them was deeply calculated by a grey relational analysis (GRA) model. The results showed that from 2006 to 2010, the economic income had the highest relational degree with food, tobacco, and alcohol in the consumption structure, which was 0.8321, and had the lowest relational degree with housing, which was 0.6216. From 2011 to 2015, the economic income had the highest relational degree with culture, education, and entertainment in the consumption structure, which was 0.9451, followed by other supplies and services, which was 0.9017, and housing, which was the lowest (0.6125). From 2006 to 2020, the economic income had the highest relational degree with daily necessities and services in the consumption structure, which was 0.8862, and the relational degree with residence was the lowest, which was 0.4125. Among different income components, the net property income had the least impact on the consumption structure. The results suggest that the consumption of rural residents in Henan Province has gradually shifted to enjoyment, and some optimization has occurred.